Mechanism of plasmin generation by S100A10 - Miller, Victoria A.; Madureira, Patricia A.; Kamaludin, Ain Adilliah; Komar, Jeffrey; Sharma, Vandna; Sahni, Girish; Thelwell, Craig; Longstaff, Colin; Waisman, David M. (Thrombosis and Haemostasis, 2017)
Plasminogen (Pg) is cleaved to form plasmin by the action of specific plasminogen activators such as the tissue plasminogen activator (tPA). Although the interaction of tPA and Pg with the surface of the fibrin clot has been well characterised, their interaction with cell surface Pg receptors is poorly understood. S100A10 is a cell surface Pg receptor that plays a key role in cellular plasmin generation. In the present report, we have utilised domain-switched/deleted variants of tPA, truncated plasminogen variants and S100A10 site-directed mutant proteins to define the regions responsible for S100A10-dependent plasmin generation. In contrast to the established role of the finger domain of tPA in fibrin-stimulated plasmin generation, we show that the kringle-2 domain of tPA plays a key role in S100A10-dependent plasmin generation. The kringle-1 domain of plasminogen, indispensable for fibrin-binding, is also critical for S100A10-dependent plasmin generation. S100A10 retains activity after substitution or deletion of the carboxyl-terminal lysine suggesting that internal lysine residues contribute to its plasmin generating activity. These studies define a new paradigm for plasminogen activation by the plasminogen receptor, S100A10.
Keywords: S100A10; annexin A2; plasminogen; plasmin; tissue plasminogen activator; plasminogen regulation